PENGARUH MODEL TGT DENGAN MEDIA SNAKE AND LADDER GAME BERBANTUAN APLIKASI QUIZ WORDWALL MATERI PERUBAHAN BENTUK ENERGI MENINGKATKAN LITERASI SAINS DAN SELF AUTHENTICITY SISWA KELAS IV SD IT AL MUBAROK KABUPATEN KEDIRI - Siti Anisy Kurlia Sa’adah; Mohamad Fatih; Khoirul Wafa (Global Action and Education for Society, 2026)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning modelcombined with the snake and ladder game and the Quiz Wordwall application on improving elementary school students' scientific literacy and self-authenticity in the topic of energy transformations. The research method used was quantitative, with a quasi-experimental design using a pretest-posttest control group design. The study subjects consisted of fourth-grade students at an elementary school in [fill in the appropriate location] Regency, divided into an experimental group and a control group. The instruments used included a science literacy test and a self-authenticity questionnaire. Data analysis showed a significant difference between the pretest and posttest results in the experimental group compared to the control group. The application of the TGT model with the snake and ladder game and the Quiz Wordwall application proved effective in improving scientific literacy and building student self-authenticity. Therefore, this model and media are recommended as an innovative alternative in thematic learning, particularly in science and science topics related to energy transformations.